Frailty as an Independent Risk Factor for Depression in Patients With End-Stage Renal Disease: A Cross-Sectional Study - Chi, Chun-Yi; Lee, Szu-Ying; Chao, Chia-Ter; Huang, Jenq-Wen (Frontiers in Medicine, 2022)
Background: Depression confers substantial disease burden globally, especially among those with chronic kidney disease (CKD). The presence of depression significantly impairs one’s quality of life. Risk factors for depression in patients with CKD remain under-appreciated, and whether frailty, a geriatric phenotype, constitutes a risk factor for depression in this population is unknown. Methods: We prospectively enrolled patients with end-stage renal disease (ESRD) undergoing hemodialysis for >3 months from National Taiwan University Hospital Yunlin Branch between 2019 and 2021. Clinical, physical, functional, and performance parameters were recorded, followed by frailty/sarcopenia assessment. Depression was screened for using the Geriatric Depression Scale. We analyzed the independent relationship between frailty and depression in these patients, using multiple regression analyses. Results: Totally 151 patients with ESRD were enrolled (mean 61.1 years, 66.9% male), among whom 16.6% had screening-identified depression. ESRD participants with depression did not differ from those without regarding most parameters except serum creatinine, functional indices, sarcopenia/frailty status. We found that having greater frail severities was independently associated with a higher probability of depression; having FRAIL- (odds ratio [OR] 5.418) and SOF-based (OR 2.858) frailty independently correlated with a higher depression probability. A linear relation exists between a greater frail severity and the probability of depression. Using a more relaxed criterion for detecting depression, higher SOF scores remained significantly associated with an increased depression risk. Conclusions: In patients with CKD, frailty independently correlated with a higher probability of having depression. Strategies aiming to attenuate frailty may be able to benefit those with depression simultaneously in this population.